Anchored phylogenomics of burrowing mayflies (Ephemeroptera) and the evolution of tusks. (24th March 2018) - Miller, Dustin B.; Bartlett, Stephanie; Sartori, Michel; Breinholt, Jesse W.; Ogden, T. Heath
Abstract: This study investigated the phylogenetic relationships among seven burrowing mayfly families. Genetic data from four ribosomal DNA genes (12S, 16S, 18S and 28S) generated with Sanger sequencing, 448 protein‐coding loci generated using a novel hybrid enrichment probe set and available RNAseq and genome assembly for 19 ingroup taxa and four outgroup taxa. Maximum likelihood and Bayesian analyses were carried out to estimate phylogenetic relationships. The results indicated that Potamanthidae, Euthyplociidae, Behningiidae and Palingeniidae were recovered as monophyletic. Ephemeridae was not monophyletic. Mandibular tusks evolved in the common ancestor of burrowing mayflies and were lost in the lineage leading to Behningiidae. Abstract : Mandibular tusks evolved in a common ancestor of the burrowers and was subsequently lost in a common ancestor of Behningiidae. The burrowing mayflies resolved as a monophyletic group. Potamanthidae, Euthyplociidae, Behningiidae and Palingeniidae were strongly supported as being monophyletic families.